Aspectos quânticos da gravidade de Chern-Simons não-comutativa - Silveira, Francisco Adevaldo Gonçalves da (2014)
In this paper we investigate what changes the gravitational potential with Chern-Simons term suffers from the addition of the noncommutative theory in space-time. We do this in two cases: the first using only the theory of Einstein-Hilbert and in the second case, adding the term topological Chern-Simons gravity type. The changes that occur are investigating on a scattering of two vector bosons exchanging a graviton. Until we reach a conclusion as the noncommutativity changes the gravitational potential, we will begin our study with a gravity model in low dimensions. After learning how to calculate the graviton propagator for quadratic theory of gravity, we expanded the concepts for a topologically massive gravity. We will review important topics of noncommutative theory in space-time. Finally analyzing the interaction with the graviton field with matter, write the vertex of the theory and find the changes arising from the noncommutativity of the two cases cited above. We found that the noncommutativity alters the shape of the gravitational potential both in origin, leaving him well behaved, as at infinity.